Penerapan Asas Proporsionalitas Dalam Penjatuhan Pidana Terhadap Pelaku Peredaran Narkotika (Analisis Putusan Nomor: 669/Pid.Sus/2018/PN.Btm) - Hendi Setiawan; Syafruddin Kalo; M Ekaputra; Edi Yunara (Iuris Studia: Jurnal Kajian Hukum, 2021)
Criminalism emphasizes preventive functions aimed at preventing the community from committing a crime. The idea of a criminal proportionality was more related to the objectives of criminal plots by the judge who was contained in his decision, as the defendant had to be sentenced to be convicted with his actions. One example of occurs in cases of perpetrators who circulated narcotics contained in Decision No. 669 / PID.SUS / 2018 / PN.BTM. Based on the background description, the problems studied, namely: how to arrange criminal plotting law against criminal acts, how the philosophy of criminal plotting against the perpetrators of criminal circulation of narcotics, and how to apply the principle of proportionality of criminal law in criminal aride against narcotics circulation perpetrators in the decision no . 669 / PID.SUS / 2018 / PN.BTM. The research method used in this study is a type of normative legal research, which is supported by primary and secondary data sources, and qualitative analysis is carried out. The results of the study, namely the regulation of criminal plotting law on the perpetrators of the crime in Article 54 of the Criminal Code Bill said that in the possession must be considered a form of error of the perpetrators, motives and the purpose of committing a criminal act, and / or the value of law and justice that lived in society. The philosophy of criminal plotting against the perpetrators of criminal circulation of narcotics as a judge in deciding a case must have consideration according to the principle of justice. Application of Proportional Propheorality of Criminal Law in Decision No. 669 / PID.SUS / 2018 / PN.BTM that it is still less proportional between criminalizations with the actions he has done, because the actions taken by the perpetrators are not due to the basis of intention and the intention arranged, but the act of the perpetrators only as people who happen to be invited without knowing what he will do